1999
DOI: 10.1038/9667
|View full text |Cite
|
Sign up to set email alerts
|

The gene mutated in adult-onset type II citrullinaemia encodes a putative mitochondrial carrier protein

Abstract: Citrullinaemia (CTLN) is an autosomal recessive disease caused by deficiency of argininosuccinate synthetase (ASS). Adult-onset type II citrullinaemia (CTLN2) is characterized by a liver-specific ASS deficiency with no abnormalities in hepatic ASS mRNA or the gene ASS (refs 1-17). CTLN2 patients (1/100,000 in Japan) suffer from a disturbance of consciousness and coma, and most die with cerebral edema within a few years of onset. CTLN2 differs from classical citrullinaemia (CTLN1, OMIM 215700) in that CTLN1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
367
4
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(379 citation statements)
references
References 25 publications
7
367
4
1
Order By: Relevance
“…aa, amino acids; EF, calcium-binding EF hand motif; TM, mitochondrial (mit) transmembrane spanner; IM, inner membrane. The figure is based on data reported by Kobayashi et al (1999), Sinasac et al (1999), Yasuda et al (2000), and Yamaguchi et al (2002) Yasuda et al 2000;Yamaguchi et al 2002) CTLN2, adult-onset type II citrullinemia; NICCD, neonatal intrahepatic cholestasis caused by citrin deficiency * CTLN2/control and NICCD/control (P Ͻ 0.01) a ratio to mutated alleles b ratio to total alleles c Four novel mutations identified will be published elsewhere …”
Section: Neonatal Intrahepatic Cholestasis Caused By Citrin Deficiencmentioning
confidence: 99%
“…aa, amino acids; EF, calcium-binding EF hand motif; TM, mitochondrial (mit) transmembrane spanner; IM, inner membrane. The figure is based on data reported by Kobayashi et al (1999), Sinasac et al (1999), Yasuda et al (2000), and Yamaguchi et al (2002) Yasuda et al 2000;Yamaguchi et al 2002) CTLN2, adult-onset type II citrullinemia; NICCD, neonatal intrahepatic cholestasis caused by citrin deficiency * CTLN2/control and NICCD/control (P Ͻ 0.01) a ratio to mutated alleles b ratio to total alleles c Four novel mutations identified will be published elsewhere …”
Section: Neonatal Intrahepatic Cholestasis Caused By Citrin Deficiencmentioning
confidence: 99%
“…With this in mind, we focused on citrin deficiency (Kobayashi et al 1999) and pyridoxine-dependent autism (Kuriyama et al 2002), a subgroup of autism expected to benefit from pyridoxine treatment, which shows similar clinical features to pyridoxinedependent epilepsy but without seizures. The findings of specific symptoms of these diseases will be reported in separate publications.…”
Section: Target Diseases and Questionnaire Itemsmentioning
confidence: 99%
“…From this, the former type II citrullinemia (MIM] 603471) can be distinguished: Kobayashi et al [1999] revealed genetic aberrations in the SLC25A13 gene, coding for citrin, a glutamate-aspartate transporter located in the mitochondrial membrane, as the underlying cause of this disease. In some patients with citrin deficiency neonatal or childhood onset is observed but most manifestations occur during adult life.…”
Section: Introductionmentioning
confidence: 99%